OTU-28 Don't ask, won't tell: Improving alcohol screening and hospital alcohol team referrals in A&E. Issue 2 (June 2019) - Robinson, Graham; Bhalme, Mahesh; Hall, Veronica; Heyes, Gemma; Gillian, Langlands; Nicola, Liggett; Osborne, Samantha
Abstract : Introduction: This Hospital's Alcohol Team provides a 7-day service, cited in the 10 Year NHS England Plan as having improved the quality of alcohol-related care. The Alcohol Team receive over 1700 referrals per year – predominantly from assessment wards where screening for potential alcohol issues of new admissions is mandatory and routine. Alcohol screening had not traditionally been routine for A&E patients. There were concerns that the introduction of mandatory screening might risk complicating patient assessment, treatment and timely discharge. Initiatives were introduced to increase the incidence of screening in A&E. An analysis was undertaken on the impact of these initiatives on referrals and patients. Methods: Initiatives introduced in 2018 1) Partnership working between A&E and Hospital Alcohol Team; Development of an Alcohol Assessment sticker, for optional incorporation into patient A&E notes, to facilitate the identification and management of potential alcohol issues ; Training targeted to A&E Nurses; A&E Link Nurse developed promotional displays and acted as a champion in A&E to raise awareness. Referral data was audited to assess the impact of the initiatives on referrals. A 10% randomised sample of referrals was further analysed to assess the impact of the increase in referrals. Case Studies were captured to illustrate the benefits of earlier identification of alcohol issues. Results: There was a 16% increase (240 patients) in total referrals received: 1523 (2017) to 1763 (2018). A&E referrals rose 79% from 217 to 389. This is against a back-drop of the rate of hospital admissions attributed to alcohol, nationally and locally, remaining broadly flat. 59% of patients referred to the Alcohol team were discharged from A&E (compared to 55% in 2017); the average length of stay of those discharged patients was 5.6 hours (compared to 6.0 hours in 2017), and 48% of these patients were discharged in under four hours (compared to 42% the previous year). Specific cases were captured in case studies to illustrate the mechanisms through which early identification of potential alcohol issues can lead to better management of alcohol-related issues, facilitate safe discharge and reduce length of stay. Conclusions: The screening, education, and partnership initiatives led to an increase in referrals from A&E to the hospital alcohol team. An audit of referrals suggests the earlier identification of alcohol-related issues in A&E has not had negative impacts on discharges and length of stay from A&E. In practice the Alcohol Team has found that earlier identification of potential issues has enabled them to intervene earlier to improve the management and timely discharge of patients.